The COMET framework: A novel approach to design an escape room workshop for interprofessional objectives. Issue 1 (2nd January 2022) - Dittman, James M.; Amendola, Michael F.; Ramraj, Rahul; Haynes, Susan; Lange, Patricia
ABSTRACT: While recreational escape rooms have gained momentum across education and team training in multiple professions, few published escape room designs have been truly interprofessional. A major obstacle faced by educators and team leaders alike is the lack of any practical design framework for escape room development that is specific to meeting learning objectives. The COMET Framework (Context, Objectives, Materials, Execution, and Team Dynamics) was developed as a step-by-step approach to escape room design using general terminology and piloted in a one-hour workshop at a regional interprofessional conference. Surveys completed by participants suggest that application of the COMET framework increased understanding and confidence regarding escape room design regardless of prior experience with the format. The generality of the COMET framework may allow it to be utilized for team exercise design more broadly in the contexts of interprofessional training and faculty development.